Analysis of determining factors for the length of job search for the first job in Badung Regency - Dewi, Anak Agung Yumita; Marhaeni, A. A. I. N. (Privietlab, 2024)
The purpose of this study is to analyze simultaneously and partially the influence of education, age, migration status, perceptions about the ease of obtaining a job, and the status of owning a 'prakerja' card on the duration of job search for the first job, to analyze the moderating role of owning a 'prakerja' card in the influence of perceptions about the ease of obtaining a job on the duration of the job search for the first job in Badung Regency, and to analyze the differences in the duration of job search for the first job among primary, secondary, and higher education graduates. This study uses a quantitative method with an associative approach. The sample size used is 105 samples with the sample determination technique using a combination of accidental sampling and snowball sampling. Data collection was conducted through observation, structured interviews, and in-depth interviews. Moderation regression analysis is the data analysis technique used. The results show that education, age, migration status, perceptions about the ease of obtaining a job, and the status of owning a 'prakerja' card have a simultaneous impact on the duration of job search for the first job in Badung Regency. Education, age, and perceptions about the ease of obtaining a job have a negative and significant effect on the duration of job search for the first job in Badung Regency. Migrant workers tend to require less time to find their first job compared to non-migrant workers in Badung Regency. Workers who own a 'prakerja' card tend to require less time to find their first job compared to workers who do not have a 'prakerja' card in Badung Regency. The status of owning a 'prakerja' card moderates the influence of perceptions about the ease of obtaining a job on the duration of the job search for the first job in Badung Regency. There are differences in the duration of job search for the first job among primary, secondary, and higher education graduates in Badung Regency.